FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN SENAM LANSIA DI POSYANDU KELURAHAN SENDANGMULYO, KOTA SEMARANG - Nadia Puspitasari; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2017)
Elderly groups who are susceptible to degenerative diseases need to maintain the quality of life in order to improve their health status. One of improving health activities for elderly is elderly gymnastics at elderly community health care. Sendangmulyo village is one of the urban villages in Semarang that regularly hold elderly gymnastics every week. The participation in elderly gymnastics can be influenced by elderly perception of disease. This study is aimed to analyze the factors associated with the utilization of elderly gymnastics at Sendangmulyo community health care, Semarang City. This research is a quantitative study with cross-sectional design. This research uses proportional sampling techniques and the data are collected using questionnaire with interview method. Data analysis procedure of this research uses univariate and chi-square test. The result shows that 58,7% respondents do not use elderly gymnastics. The result of chi-square test shows that perceived barrier (p= 0,002) and environmental support (p= 0,012) are significantly associated with the utilization of elderly gymnastics (p-value < 0,05). While age (p=1,000), gender (p= 0,140), marital status (p= 0,473), education level (p= 0,290), respondents knowledge about elderly gymnastics (p= 0,689), perceived susceptibility (p= 0,060), perceived severity (p= 0,125), perceived benefit (p= 0,831), and family support (p= 0,075) are not significantly associated with the utilization of elderly gymnastics. Suggestion from this research is the need to give more education about elderly gymnastics from related parties, especially for elderly, to improve their awareness to utilize elderly gymnastics.